ENGLISH AND COMMUNICATION SKILL WITH TOURIST AS NATIVE SPEAKER BASED ON CONTEXTUALS LEARNING APPROACH - Faidah Yusuf (UIN Alauddin Makassar, 2017)
AbstractThis study about the communication skill of using English with tourist as native speaker based on context. In this presentation, the lecturer gives the task to the students to find the tourists to invite to communicate, in places where the context of tourist attractions. So, they are free and easy can practice their English which of course uses communication skills. The students made the group, and go together in the tourist attraction and record and take the picture with the tourist. Then students make material and mental preparations before communicating with tourists, and present their English communication results in class. Students are highly motivated in communicating with tourists as native speaker.AbstrakStudi tentang kemampuan berkomunikasi menggunakan bahasa Inggris dengan turis sebagai penutur asli berdasarkan konteks. Dalam presentasi ini, dosen memberikan tugas kepada para siswa untuk mencari wisatawan untuk diajak berkomunikasi, di tempat-tempat di mana konteks tempat wisata. Jadi, mereka bebas dan mudah bisa mempraktekkan bahasa Inggris mereka yang tentu saja menggunakan kemampuan komunikasi. Para siswa membuat kelompok tersebut, dan pergi bersama-sama di tempat wisata dan merekam dan berfoto bersama turis. Kemudian siswa membuat persiapan materi dan mental sebelum berkomunikasi dengan turis, dan mempresentasikan hasil komunikasi bahasa Inggris mereka di kelas. Siswa sangat termotivasi dalam berkomunikasi dengan wisatawan sebagai penutur asli.